An efficient approach for traveling salesman problem solution with branch-and-bound - Mustafa, Mamat; Suyudi, M.; Sukono, . (2016)
Travelling salesman problem is a known problem. In this paper will be used method of branch-and-Bound efficient to solve the problem Traveling salesman. Tour starts from a given starting vertex and all vertices to be passed, then returned to the initial vertex. Costs given a different path. Furthermore ,will be found to the tour cost is minimal between the city (node) connected.